From physicist to patent attorney. (March 2021) - Phillips, Monifa
Abstract : Monifa Phillips beat the odds, becoming the first Black woman to graduate with a PhD in physics from the University of Glasgow. She describes her pathway into physics, her successes and struggles in academia, and her future in patent law